The more the better: Role of polymer concentration in degradation of drag reducing agents - Besla,J; Brandfellner,L; Bismarck,A; Müller,HW (Journal of Non Newtonian Fluid Mechanics, 2026)
Polymer concentration is a key parameter for the application of polymeric drag reducing agents. Drag reducing agents are high molecular weight polymers which reduce drag in turbulent flow. Increasing polymer concentration increases drag reduction (DR) as well as polymer stability, counteracting polymer chain scission in turbulent flow. We investigated DR and stability of polyethylene oxide (PEO) in dilute and semi-dilute solutions in the concentration range of 25 wppm to 200 wppm using the pilot scale Vienna Experiment for Drag Reducing Agents (ViEDRA), taking into account viscosity changes caused by polymer concentration variation and polymer degradation. Theories attempt to reveal the mechanism of DR and to describe polymer degradation in turbulent flow. Most numerical simulations of DR do not account for polymer degradation and many experimental studies neglect viscosity changes. We focus on the impact of polymer concentration on both initial DR of the un-degraded polymer and on polymer degradation rate. Solution viscosity is monitored to disentangle DR provided by polymer dynamics from artefacts caused by viscosity changes with polymer addition, revealing a clear influence of polymer concentration on both initial DR and polymer degradation rate. The highest initial DR value was observed in solutions with the highest polymer concentrations. Degradation rate was higher for low polymer concentrations.